Marinobacter adhaerens sp. nov., isolated from marine aggregates formed with the diatom Thalassiosira weissflogii - Eva C. Sonnenschein (International Journal of Systematic and Evolutionary Microbiology, 2012)
A Gram-negative, motile, rod-shaped bacterial strain, HP15T, was isolated from aggregates taken from surface waters of the German Wadden Sea (German Bight). Of 82 marine isolates, HP15T was chosen for further study because of its high potential to induce production of transparent exopolymeric particles and aggregate formation while interacting with the diatom Thalassiosira weissflogii. HP15T grew optimally at 34–38 °C and pH 7.0–8.5, and was able to tolerate salt concentrations of 0.5–20 % (w/v) NaCl. HP15T was characterized chemotaxonomically by possessing ubiquinone-9 as the major respiratory lipoquinone, as well as C16 : 0, C18 : 1ω9c and C16 : 1ω7c/iso-C15 : 0 2-OH as the predominant fatty acids. The DNA G+C content of strain HP15T was 56.9 mol%. The closest relative based on 16S rRNA gene sequence analysis was the type strain of Marinobacter flavimaris, with 99 % similarity. Whole-genome relatedness values of HP15T to the type strains of M. flavimaris, Marinobacter salsuginis, Marinobacter lipolyticus and Marinobacter algicola were less than 70 %, as determined by DNA–DNA hybridization. On the basis of phenotypic and chemotaxonomic properties as well as phylogenetic analyses, the isolate represents a novel species, Marinobacter adhaerens sp. nov.; the type strain is HP15T ( = DSM 23420T = CIP 110141T).